Liver transplantation after paracetamol overdose. Issue 6796 (27th July 1991) - O'Grady, J G; Wendon, J; Tan, K C; Potter, D; Cottam, S; Cohen, A T; Gimson, A E; Williams, R
Abstract : OBJECTIVE–To evaluate the role of liver transplantation after paracetamol overdose. DESIGN–Prospective study of consecutive candidates for transplantation and performance of transplantation over 18 months. SETTING–Liver unit, King's College Hospital, London. MAIN OUTCOME MEASURES–Fulfilment of indicators of poor prognosis, selection for transplantation, transplantation, survival. RESULTS–30 of 37 patients considered to have a reasonable prognosis with intensive medical care survived. Of 14 of 29 patients considered to have a very poor prognosis and registered for urgent liver transplantation, six received liver transplants, four of whom survived, while seven died and one survived without a transplant. Three of 15 patients with poor prognostic indicators but not selected for transplantation survived. CONCLUSION–Liver transplantation will have a definite but limited role in the management of fulminant hepatic failure induced by paracetamol.